Improvement of Biodegradability of Antibiotics Wastewater by Photo Fenton Process - Elmolla, E. S.; Chaudhuri, M. (2008)
Antibiotics are emerging contaminants in the aquatic environment because of their adverse effects on aquatic life and humans. Antibiotics wastewater has high COD and very low BOD5, and hence is difficult to treat biologically. The objective of this research was to study the effect of operating conditions (reaction time, pH, H2O2 dose and Fe2+ dose) of the photo Fenton process in improving the biodegradability of a synthetic amoxicillin wastewater. The results show that the biodegradability ratio (BOD5/COD) improved from 0 to 0.36, 0.51 and 0.60 in 15, 45 and 75 min reaction time respectively. The biodegradability ratio was 0.51 when H2O2 concentration 50, mM and 0.55 at Fe2+ concentration 0.5 mM, and 0.53 when pH value 3.50. The photo Fenton process is considered a suitable pretreatment method to improve the biodegradability of antibiotics wastewater.